Tipificación del modelo de negocio de ventas de bienes o servicios en esquema piramidal dentro del COIP - Coveña Bravo, Melissa Michell (2019)
Among the different forms of commerce that exist today, multi-level marketing has become popular. This form of trade consists of a sales plan that rewards benefits to sellers for the sales of their products and the number of people entering the sales plan, of course, prior to the entry of the sales plan, future sellers must acquire the product s, which makes them consumers. However, the excessive greed of the merchants and the lack of control on the part of the authorities, has resulted in the multi-level sale, which is a sales scheme that is valid and legal in many countries, resulting in a business harmful to the society, as is the pyramid sales system. The pyramid sales system consists of a sales organization that works similarly to multi-level sales, but in addition to this, there is a marketing strategy that aims to enter the largest number of people into the sales plan excessive, under the promise of obtaining benefits, but when making a massive entry of people what these sales schemes are looking for is that there is a continuous flow of money from the entry of new participants, which will be paid later to the previous participants when Claim your benefits……..